Intrapersonal Factors Relationship in Adolescent Pregnancy - Nyoman Anita Damayanti; Yuly Sulistyorini; Windhu Purnomo; Rachmat Hargono; Iswari Hariastuti; Diyah Herowati; Mardiyono Mardiyono; Udin Kurniawan Aziz; Wandera Ahmad Religia (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2022)
IDHS (2017) shows that there is most unwanted pregnancy among young women in the age group of 15-19 years (16.4%). The unwanted pregnancy can be caused by several factors. Malang Regency had a 15-19 year ASFR of 47.71 in 2018, which was higher than the national target. For this reason, it is significant to conduct research for addressing adolescent pregnancy and to analyze the relationship between interpersonal factors (level of education, employment status, and dating experience) and adolescent pregnancy. The researchers used a case-control design in 50 villages in 15 subdistricts of Malang District. The respondents consisted of 114 adolescent women (20-25 years old) divided into case groups (who had been pregnant at age 19 years) and the control group (who did not get pregnant at age 19 years). They were then interviewed using questionnaires, and the data were analyzed using statistical tests. The results showed that there is a significant relationship between the level of education and adolescent pregnancy (p = 0.000 < α, C = 0.618). On the other hand, there is no relationship between employment status (p = 0.424), dating experience (p = 0.438), and adolescent pregnancy. Therefore, adolescents do not only need to be encouraged to pursue higher education to improve adolescent self-quality but they also need to prevent themselves from pregnancy.